87-n=13

Simple and best practice solution for 87-n=13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 87-n=13 equation:


Simplifying
87 + -1n = 13

Solving
87 + -1n = 13

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-87' to each side of the equation.
87 + -87 + -1n = 13 + -87

Combine like terms: 87 + -87 = 0
0 + -1n = 13 + -87
-1n = 13 + -87

Combine like terms: 13 + -87 = -74
-1n = -74

Divide each side by '-1'.
n = 74

Simplifying
n = 74

See similar equations:

| 24n^3+30n^2=0 | | -21a+28a-6=10 | | 4[(12+5)-1024]= | | 5y-15+6=5y+8-1x+17 | | 4x^2+6x+1=2x^2+6x-6+1 | | 8p+5-3=9+7p | | 3(d-2)=15 | | 3s+5w=19 | | 5x-54+3x+16=180 | | 2x^2=x^2-6 | | -4y=-x+6+zy | | 16x^4+32x^3+24x^2+8x-80=0 | | tan(x)=-0.364+0.57735027 | | 6-3u=21 | | n-6=13-4 | | 5-3(2x-4)=5(4x+2)-32 | | 80+.10x=132 | | 4x+48=828 | | (x^2-200x+4000log(x)-7200)=0 | | X+12y=23 | | -3a-7a=-3a-6a+7 | | 8u+2-4(-3u+2)=4(u-1) | | 9z+4-8=27 | | M+8=2m+1 | | -2(4s-5)-10=-2(6s+2)-2 | | 2x(x-3)=1+4x | | t^2-6t-4=0 | | F(-3)=9x-5 | | 12X^2-48X+34=0 | | 9y+2x(5y-19)=38 | | .45x+.05(14-x)=.10(79) | | X+.4444=.75 |

Equations solver categories